TLR2-induced cytokine responses may characterize HIV-infected patients experiencing mycobacterial immune restoration disease - Tan, Dino B.A.; Lim, Andrew; Yean, K. Yong; Ponnampalavanar, Sasheela; Omar, Sharifah Faridah Syed; Kamarulzaman, Adeeba; French, Martyn A.; Price, Patricia (Lippincott Williams & Wilkins, 2011)
Objectives: Most HIV patients who experience Mycobacterium tuberculosis-associated immune restoration disease (TB IRD) display elevated interferon-gamma (IFN gamma) responses against mycobacterial antigens, but these can occur without an IRD. Recognition of mycobacteria-associated molecular patterns through toll-like receptors (TLRs) on dendritic cells and monocytes induces cytokine production. Here, we investigate TLR-induced responses in IRD. Design: Peripheral blood mononuclear cells (PBMCs) were collected at approximately weeks 0, 6, 12, 24 and 48 after antiretroviral therapy from five patients experiencing TB IRD, nine matched non-IRD patients and 15 healthy controls. Methods: IFNg production by PBMC stimulated with protein purified derivative (PPD) was assessed by ELISpot. TLR2 expression on myeloid dendritic cells (mDCs) and monocytes was assessed by flowcytometry. TNF alpha, IL-12p40 and IL-10 were measured by ELISA in 24-h cultures of PBMC with lipomannan (mycobacteria-derived TLR2 agonist). Results: TLR2 expression on mDC and monocytes was higher in patients than controls at baseline (P<0.005). TLR2 expression decreased to normal levels on mDC by week 12, but remained higher on monocytes at week 24 (P=0.02). At week 24, IRD patients showed higher IFNg responses to PPD (P=0.02), TLR2 expression on monocytes (P=0.006) and lipomannan-induced TNF alpha production (P=0.016) than non-IRD patients. Lipomannan-induced TNF alpha and IL-12p40 responses paralleled TB IRD in the patients with high TLR2 expression. IL-10 levels did not associate with IRD. Conclusion: TLR2-induced pro-inflammatory cytokines by dendritic cells or monocytes may contribute to the pathogenesis of mycobacterial IRD. (C) 2011 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins